Investigating Students’ Self-Efficacy on the Use of Oral Peer Feedback in Speaking Subject - Ratih Ratih; Andi Rustandi; R. Bunga Febriani (Yayasan Karinosseff Muda Indonesia, 2020)
The study attempted to investigate students' self-efficacy on the use of oral peer feedback in speaking subject. Afterward, The researcher used a questionnaire to find out the level of student self-efficacy in giving oral peer feedback and the interview to find out how students with high and low self-efficacy give their oral peer feedback. This study employed qualitative strategies by using case study. The participants were 25 students who had used oral peer feedback in their speaking subject. The findings revealed that the students’ self-efficacy played such a big role in giving oral peer feedback in speaking subject. Their beliefs influence the process of achieving their goals and their performance as well. Furthermore, students with high self-efficacy tend to believe that they can handle any situation that they face effectively, use certain strategies, and learn from their experiences. Although, the students with low self-efficacy did not have certain strategies to face their performance which lead them into failure. Thus, the failure caused them to feel anxiety, sad, apathetic and worried all the time. Based on the findings self-efficacy has a great effect on the students’ achievement and performance in giving oral peer feedback in speaking subject and even the other courses.